Effect of Repeated Moist Heat Sterilization on Titanium Implant–Abutment Interface—An In Vitro Study - Morsy, Mohamed S.M.; Hassan, Ali Abdel-Halim Abdel-Azim; Alshawkani, Hamed A.; Mattoo, Khurshid A.; Mathur, Ankita; Fiorillo, Luca (European Journal of Dentistry, 2024)
Objectives Sterilization eliminates microbial viability by decreasing the biological load, but likewise have the ability to deteriorate the mechanical properties of an implant material. This study intended to evaluate the effect of repeated moist heat sterilization on implant–abutment interface using two different implant systems.Materials and Methods Forty screw-retained titanium implant–abutment combinations (fixture 3.5 ×10 mm, abutment 2 mm diameter), twenty each from Genesis (Aktiv Implant Systems, United States) and Bredent (SKY, Germany), were divided into four different groups (n = 10) and placed in a computer-aided diagnostic model. The abutments from each group were exposed to first and second autoclave cycle (121°C for 30 minutes), connected back to the fixture and analyzed under scanning electron microscope for marginal gap and surface roughness.Results Genesis group showed higher marginal gaps on both sides (buccal/mesial [2.8 ± 0.47]; lingual/distal [2.8 ± 0.33]), while Bredent implant–abutment system (IAS) did not show any changes in marginal gaps after autoclaving. Differences within and between the group were found to be statistically significant. Surface roughness for Genesis (243.7 ± 70.30) and Bredent groups (528.9 ± 213.19) was highest at second autoclave, with Bredent implant–abutment showing higher values for surface roughness than Genesis IAS.Conclusion Marginal vertical gap increased with autoclaving for Genesis IAS, while Bredent implant abutments were more stable. Surface roughness increases with autoclaving for both Genesis and Bredent group of IAS.
Keywords: titanium abutments; implant–abutment interface; sterilization; marginal gap; surface roughness; dental implant